(untitled) (Universal International Scientific Journal, 2026)
This study presents a comprehensive comparative analysis of group III–nitride semiconductors, namely gallium nitride (GaN), indium nitride (InN), and aluminum gallium nitride (AlGaN), focusing on their structural, electronic, and optical properties. Owing to their wide and tunable band gaps, high thermal and chemical stability, and pronounced spontaneous and piezoelectric polarization effects, III–nitride materials play a crucial role in modern high-power, high-frequency electronic and optoelectronic devices. The analysis includes a systematic comparison of crystal structures, lattice parameters, band gap energies, carrier mobility, and optical absorption characteristics of GaN, InN, and AlGaN. Special attention is devoted to AlGaN ternary alloys, where the influence of aluminum composition on band gap engineering, strain effects, and polarization-induced charge is examined. The advantages of these materials in forming heterostructures and quantum well systems are discussed in the context of device applications such as light-emitting diodes, laser diodes, ultraviolet photodetectors, and high-electron-mobility transistors (HEMTs). The results highlight the distinctive features and technological potential of each material, providing a solid scientific basis for the design and optimization of advanced III–nitride–based semiconductor devices